Psicanálise, literatura e educação: : uma escrita para a despatologização do sintoma disortográfico - Fernandes, Andréa (2020)
The article starts from the premise that the continuous dialogue between psychoanalysis and literature has contributed to the depatologization of the concept of the symptom in psychoanalytic theory. The questions that are examined in the text are: How far can this exchange between literature and psychoanalysis have resonances in investigations based on psychoanalysis and related to other fields of knowledge, such as education? Could a path through the dialogue between psychoanalysis and literature support a depatologization of the symptom in times of growing expansion and the use of diagnosis in education, especially around learning disorders such as disortographic symptoms? Through a clinical approach, it examines and defends some contributions from the theory of the psychoanalytic clinic that can help in the management of the callejones without knowing during the literacy, which also circumscribe the logical moment to affect the psychic structure of the child.